Exploring Sertoli Cells’ Innate Bulwark Role Against Infections: In Vitro Performances on Candida tropicalis Biofilms - Iva Arato; Stefano Giovagnoli; Luca Roscini; Mario Calvitti; Catia Bellucci; Cinzia Lilli; Elena Eugeni; Stefano Brancorsini; Gianluigi Cardinali; Giovanni Luca; Francesca Mancuso (Cells)
This study aimed to evaluate the intrinsic in vitro performance of naïve porcine prepubertal Sertoli cells (SCs) and SCs loaded with blank poly(lactic acid) microparticles (MP) or amphotericin B poly(lactic acid) microparticles (AmB-MP) against Candida tropicalis, a prevalent pathogenic non-albicans species. The objective was to assess their impact on biofilm formation and the cellular response mechanisms involved, building on previous findings that highlight SCs’ potential as anti-infective agents and drug carriers. Our results demonstrated that SCs successfully internalized Candida tropicalis while maintaining viability and exhibited a strong anti-infective effect, inhibiting biofilm formation by 70%. This inhibition increased to 80–90% when SCs were combined with AmB-MP. The interaction between SCs (both naïve and MP-loaded) and Candida tropicalis triggered the activation of MAPK, AKT, and NF-kB signaling pathways, leading to the upregulated expression of innate immune factors such as MHC-II, TLR-4, TGF-β, IDO, and β-defensin 123. These findings reinforce the role of SCs in infection control and drug delivery. Furthermore, their anti-infective and scavenging activity is linked to a tolerogenic phenotype, suggesting a potential dual therapeutic role at the host–pathogen interface.